Національно-демократична революція на західно-українських землях 1914–1923 рр.: до проблеми концепту - Реєнт, О.; Великочий, В. (Краєзнавство, 2018)
У статті головна увага приділяється з'ясуванні основних здобутків «вузьких місць» та перспектив подальшого вивчення комплексу питань, пов'язаних з державотворчими процесами у Галичині за воєнно-революційної доби 1914–1923 рр. The cornerstone of the renewed concept of a national-democratic revolution in West Ukrainian lands is its perception and design in the context of the general continental process of the European peoples’ struggle for their national liberation and state self-affirmation during the First World War. Within the framework of this approach, the lower boundary of the process (national liberation struggle in the West Ukrainian lands) and the phenomenon (November 1918, the national democratic revolution) should not only be united, but also mutually determined. Moreover, they should be considered in the context of continuity and subsequence. Hence, in this case the possible use of the term «National democratic revolution in the West Ukrainian lands of 1914– 1923» is being analyzed in the article. On one hand, thanks to such an interpretation of the chronological boundaries of the national-democratic revolution in the WestUkrainian lands, logically there arises the need to clarify the boundaries of the entire Ukrainian revolution of the second or third decade of the 20thcentury. First of all, because its constituent and integral part is the revolutionary events in the West Ukrainian lands of this period. On the other hand, it is these events that extend the boundaries of the actual Ukrainian revolution on its national scale, and establish its paradigm as a national liberation, national-state, and community-unity one.